Organizational commitment: do employees’ compensations and benefits matter? - Rahaman, Mohammad Saidur; Abdul, Mohani; Rahman, Mohammad Mizanur (International Organization of Scientific Research, 2016)
The main objective of this research is to identify Bangladesh Railway employee's commitment based on compensation and benefits. A structured questionnaire was used to survey the opinions of 40 employees who are from Bangladesh Railway, Rajshahi City. The researchers conducted various statistical analyses such as descriptive statistics, correlation and multiple regression analysis to analyze the survey responses and identified a number of key findings. The study reveals that there are various common factors related to the compensations and benefits that affect employee's commitment.